COMPREHENSIVE ASSESSMENT OF THE EFFECTIVENESS OF LOCALIZATION PROCESSES AT THE ENTERPRISES OF JSC UZAVTOSANOAT (European Journal of Economics, Finance and Business Development, 2025)
This article presents a comprehensive assessment of the effectiveness of localization processes implemented at the enterprises of JSC Uzavtosanoat. As a leading automotive manufacturer in Uzbekistan, Uzavtosanoat has adopted localization strategies to enhance its production capabilities, reduce dependency on imports, and boost the local economy. The study evaluates various dimensions of the localization process, including supply chain optimization, quality enhancement, cost reduction, and social impact. Through qualitative and quantitative analysis, the article identifies key achievements, challenges, and areas for improvement within the localization framework. The findings underscore the significance of localization in fostering sustainable growth and competitiveness in the automotive sector.